POLA NARASI PADA ANTOLOGI CERPEN TARIAN SALJU KARABAN - Novi Diah Haryanti (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2019)
Abstract: This study aims to look at narrative patterns in the collection of short stories